Les demandes d'enfermement dans la généralité de Rouen au XVIIIe siècle : le récit de vie comme objet d'Histoire - Élise Chopin-Tufel (L'Atelier du CRH)
Through Norman examples from the second half of the 18th century, this article analyses the structure of confinement requests cases and the reasons why families used lettres de cachet to lock up one of their folks. Those documents show particularities (a lack of spontaneity, a fragmentation in the narrative) that must be considered when studying them. However they are very useful to study social networks as well as the standards and contraventions of this prerevolutionary Norman society. This concept of a 'narrative identity' as developped by Paul Ricœur enriches the study of these sources. Through narration, Normans who are to be tried use different identities, which give information about their relations with politics